Griechen im Heiligen Römischen Reich - Saracino, Stefano (De Gruyter, 2024)
This is the first volume to deal with the migration of Greeks to the Holy Roman Empire in detail. It reveals that there were three types of migrants: almsmen, students, and traders. Greek migrants from the Ottoman Empire were of particular significance as "bearers of knowledge," with scholars and institutions viewing their presence as a great opportunity. The book also describes the resulting interactions and relationships.